New evidence on the Late Bronze – Early Iron Age human nutrition in the Crimea (northern Pontic Region) based on the stable isotope analysis and radiocarbon dating - Kulkova Marianna A.; Kashuba Maya N.; Kulkov Aleksandr M.; Kozhukhovskaya Yuliya V.; Tikhomirov Vitaliy A.; Streltsov Mihail A. (Поволжская археология)
The application of geochemical methods (stable isotope δ13C, δ15N analysis, chemical elemental analysis and radiocarbon dating) for studying human and animal bones from burials and cultural layers of archaeological sites of Crimea made it possible to highlight the issues of the development of agriculture and cattle-bгeeding during the Late Bronze – Early Iron Ages. One of the controversial questions is the problem of transition from sedentary forms of agriculture and cattle-breeding to mobile cattle-breeding among ancient communities in the Eurasian steppe and forest-steppe. On the base of data obtained various groups of people were identified, which are characterized by different nutritional systems, primarily related to the specifics of their economic activities. The inhabitants of the settlements are characterized by the predominance of fish, seafood, milk and meat. Coastal individuals had access to marine food and C4 plants that they consumed. The presence of various indirect evidence related to land cultivation such as tools for agriculture, suggests the presence of agriculture and the cultivation of millet at the Bai-Kiyat I settlement of the Late Bronze Age by the bearers of the Late Sabatinovka and Early Belozerka cultures. Another group of people from this settlement is associated with pastoral activities. Their diet includes more meat and dairy products, as well as plant foods with photosynthesis of C3. Our research suggests the presence of seminomadic cattle-breeding among the communities of the Sabatinovka and Belozerka cultures of the Late Bronze Age and transhumance pastoralism among the bearers of the Kizil-Koba culture of the Early Iron Age.